Caracterização das falhas de transferência na porção norte da Bacia de Santos a partir da integração de dados geológicos e geofísicos - De Souza, Iata Anderson [UNESP]; Ebert, Hans Dirk [UNESP]; De Castro, Joel Carneiro [UNESP]; Soares Jr., Adilson Viana [UNESP]; Silva, Gustavo Henrique Teixeira Da; Benvenutti, Carlos Felipe [UNESP] (My University, 2008)
Structures transverse/sub-transverse to the shoreline have been identified and characterized on the precambrian basement outcrop on the continent adjacent to the northern Santos Basin. These structures were analyzed from images of digital elevation model SRTM 90m by extracting NW-SE lineaments that intersect the NE-SW foliation. The lineaments were selected, classified into 48 segments that extend toward offshore, and correlated with basin structures. In the basin 25 2D seismic sections, 12 well logs and data from potential methods were interpreted, identifying the key stratigraphic levels and the major structures. Structural maps of each horizon were generated. Six transfer faults (FTs) were recognized and named FT-1 to FT-6, whose extensions correspond to continental lineaments named FC1 to FC6. The FTs are related to the basin deformation and evolution. In seismic sections, these faults have lateral slip in flower structures, displacement inversions from normal at the top to reverse at the base, abrupt changes in thickness or even disappearance of the seismic reflectors. The structural map of the Basement and Top of the Rift shows control of some depocenters by faults and displacements in some areas. The maps of potential methods indicate that there are pronounced anomaly shifts in some areas, associated with FTs. Some seismic sections indicate reactivation of FTs when they intersect horizons from the basement until the most recent layers. The 3D integration of data facilitated the observation of the FT extensions in the continent discontinuity.
Transfer faults characterization in northern portion of the Santos Basin based on geological and geophysical data integration
Keywords: Santos basin; Tectonic lineaments; Transfer faults; basin evolution; conference proceeding; deformation; digital elevation model; displacement; fault propagation; foliation; image analysis; lineament; outcrop; Shuttle Radar Topography Mission; slip; stratigraphy; tectonic setting; Atlantic Ocean; Santos Basin